AUDITING IN THE PUBLIC INTEREST: AN ANALYSIS OF RESEARCH ON THE CODE OF ETHICS OF THE PUBLIC ACCOUNTING PROFESSION - Febriyanti, Diah; Syarif, Devyanthi (Journal of Accounting Inaba, 2022)
The public interest should be one of the main priorities in the process and determination of the results of an audit conducted by a Public Accountant. This research investigated public interest as a determining factor during the audit process. This is important due to many cases of audit failures existed were caused by breaches of the code of ethics by Public Accountants, which eventually caused harm to the public interest. The phenomenon of audit failure was not only experienced by the Office of Public Accountants (KAP) at small and medium scales but also by those included in the Big Four category with similar indications, breaches of the code of ethics by public accountants.